Canine osteosarcoma in comparative oncology: Molecular mechanisms through to treatment discovery - Simpson, Siobhan; Rizvanov, Albert A.; Jeyapalan, Jennie N.; de Brot, Simone; Rutland, Catrin S. (Frontiers in Veterinary Science, 2022)
Cancer is a leading cause of non-communicable morbidity and mortality throughout the world, similarly, in dogs, the most frequent cause of mortality is tumors. Some types of cancer, including osteosarcoma (OSA), occur at much higher rates in dogs than people. Dogs therefore not only require treatment themselves but can also act as an effective parallel patient population for the human disease equivalent. It should be noted that although there are many similarities between canine and human OSA, there are also key differences and it is important to research and highlight these features. Despite progress using chorioallantoic membrane models, 2D and 3D in vitro models, and rodent OSA models, many more insights into the molecular and cellular mechanisms, drug development, and treatment are being discovered in a variety of canine OSA patient populations.